Taylor - Math 17B Kouba Taylor Polynomials QUESTION :...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Math 17B Kouba Taylor Polynomials QUESTION : Consider the function y 2: f (:12) and assume that mathematical circum— stances would require that this function be replaced with an nth-degree polynomial whose values closely approximate the values of y = f (:13). How would we determine the coefficients of this unknown polynomial ? ANSWER : Assume that y = f (:c) is a given function and constant “a” is known. Deter- mine a list of real numbers (10, a1, a2, a3, - - - , an so that the polynomial is Pn(m) = a0 + a1(a: — a) + (12(11,‘ —‘ a)2 + a3(x — (1)3 + - - - + an(:c — a)" , which satisfies the condition f($) W RICE), i.e., (T) f(m) z a0 +a1(a: — a) +a2(:v—a)2 +a3($— (1)3 +---+an(m -— a)". If we assume that “ z ” is “ =” and substitute a: = a in equation (T), we get f(0) = 00 + (11(0) + a2(0)2 + ay3(0)3 + . . . + an(0)n = a0, i.e., a0 = f(a) . Now differentiate equation (T) term by term getting f’(x) = a1 + 2a2(a: — a) + 3a3(a: — (1)2 + 4a4(:1: — a)3 + - - - + nan(m — a)"'1. If we substitute :5 = a in this equation, we get f’(a) = a1 + 2a2(0) + 3ag,(0‘)2 + 4a4(0)3 + - - - + nan(0)"'1 = a1 , i.e., a1 = f’(a) . Now differentiate again term by term getting f”(a:) = 2a2 + 3- 2a3(:t: — a) + 4 - 3a4(a: — (1)2 + 5 - 4a5(a: —— (1)3 + - - -+ n- (n - 1)anx"’2. If we substitute :1: = a in this equation, we get f”(a) = 2612 +3 - 2a3(0) +4-3a4(0)2 +5-4a4(0)3 + - - .+ (n — 1) -nan(0)”'2 = 202, = [7(0) 2! ' Now differentiate again term by term getting i.e., 02 f”’(a:)=3-2a3+4-3-2a4(x—a)+5~4-3a5(:1:—a)2+~~+n(n—-1)(n—2)ana:""3. 1 If we substitute a: = a in this equation, we. get f’”(a) = 3-2a3+4-3-2a4(0) +5-4-3a5(0)2 +~ -n(n—1)(n-2)an(0)"‘3 = 3~2a3, i.e., Continuing this term by term differentiation and substitution process results in the fact that (k) a ) forki=0,1’2,3’-..,n' DEFINITION : The Taylor Polynomial of degree n centered at x = a for function y = f (:13) is given by (P) Pn(m) = a0 + a1(a: ~— a) + (12(30 —- (1)2 + a3(w - (1)3 + - - - + an(:r —— a)“ and (k) (S) ak=fk'(a) forlc=0,1,2,3,--~,n. QUESTION : Consider an ordinary function y = f and Pn(:v), its Taylor Polynomial of degree n centered at a: = a. We assume that f z Pn Let the error be given by Rn+1(:r;a) = f —— Pn(:c). It can be shown that the absolute error (Taylor Error) for their diflerence is Rn+1($; 0). = (1’3 ‘ a)n+1 3 where c is some number between :1: and a. (Note that the number c appears as a result of using the Intermediate Value Theorem to derive this error formula.) ...
View Full Document

Page1 / 2

Taylor - Math 17B Kouba Taylor Polynomials QUESTION :...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online